2019
DOI: 10.1128/mbio.00266-19
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Imaging Reveals Divergent Cytokine and Cellular Immune Responses to Candida albicans and Candida parapsilosis

Abstract: Candida yeasts are common commensals that can cause mucosal disease and life-threatening systemic infections. While many of the components required for defense against Candida albicans infection are well established, questions remain about how various host cells at mucosal sites assess threats and coordinate defenses to prevent normally commensal organisms from becoming pathogenic. Using two Candida species, C. albicans and C. parapsilosis, which differ in their abilities to damage epithelial tissues, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 137 publications
(164 reference statements)
0
14
0
Order By: Relevance
“…Imaging by time-lapse at the single cell level revealed that tnfα-expressing cells are motile and are absent when macrophages are depleted, suggesting that only macrophages express tnfα in both yeast-locked and wildtype fungal infections. Although imaging of tnfα levels in macrophage transgenics was not performed here, nearly all tnfα-GFP+ cells were found to also be mpeg1:mCherry+ in a similar swimbladder infection model [46]. Proinflammatory cytokines at the infection site likely promote vascular permeability that may enhance fungal spread to the bloodstream by endocytic, paracellular and/or Trojan-horse pathways [7,22,23,47].…”
Section: Discussionmentioning
confidence: 88%
“…Imaging by time-lapse at the single cell level revealed that tnfα-expressing cells are motile and are absent when macrophages are depleted, suggesting that only macrophages express tnfα in both yeast-locked and wildtype fungal infections. Although imaging of tnfα levels in macrophage transgenics was not performed here, nearly all tnfα-GFP+ cells were found to also be mpeg1:mCherry+ in a similar swimbladder infection model [46]. Proinflammatory cytokines at the infection site likely promote vascular permeability that may enhance fungal spread to the bloodstream by endocytic, paracellular and/or Trojan-horse pathways [7,22,23,47].…”
Section: Discussionmentioning
confidence: 88%
“…Future studies should be directed at determining what type of effect 5αDHT has on various immune cells, including dendritic cells, macrophages and neutrophils, as these are key cells in the immune resistance to C. albicans infections [ 32 , 33 , 34 ]. Discerning the differences in immune responses between females and males is needed as current treatments including drug and vaccination treatments do not generally consider sex-differences [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models, neutrophils were identified as key players in controlling disseminated candidiasis, and neutropenia is known to be a major risk factor for systemic candidiasis [ 27 , 28 , 29 , 30 , 31 ]. Besides neutrophils, monocyte-derived immune cells play an essential role in host defense against C. albicans infections.…”
Section: The Pathogen C Albicans and Innate Immentioning
confidence: 99%